Advances in Cellular Therapy for the Treatment of Thyroid Cancer. (29th June 2010) - Papewalis, Claudia; Ehlers, Margret; Schott, Matthias
Abstract : Up to now, there are no curative therapies available for the subset of metastasized undifferentiated/anaplastic thyroid carcinomas. This review describes the possible use of immunocompetent cells which may help to restore the antitumor immune recognition for treating an existing tumor or preventing its recurrence. The most prominent experimental strategy is the use of dendritic cells (DCs) which are highly potent in presenting tumor antigens. Activated DCs subsequently migrate to draining lymph nodes where they present antigens to naïve lymphocytes and induce cytotoxic T cells (CTL). Alternatively to DC therapy, adoptive cell transfer may be performed by either using natural killer cells or ex vivo maturated CTLs. Within this review article we will focus on recent advances in the understanding of anti-tumor immune responses, for example, in thyroid carcinomas including the advances which have been made for the identification of potential tumor antigens in thyroid malignancies.